2016
DOI: 10.1073/pnas.1508541113
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal breast cancer metastases arise from collective dissemination of keratin 14-expressing tumor cell clusters

Abstract: Recent genomic studies challenge the conventional model that each metastasis must arise from a single tumor cell and instead reveal that metastases can be composed of multiple genetically distinct clones. These intriguing observations raise the question: How do polyclonal metastases emerge from the primary tumor? In this study, we used multicolor lineage tracing to demonstrate that polyclonal seeding by cell clusters is a frequent mechanism in a common mouse model of breast cancer, accounting for >90% of metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
701
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 640 publications
(781 citation statements)
references
References 54 publications
44
701
3
Order By: Relevance
“…43). Collective migration may be the rule rather than the exception in metastasis, despite the physical challenges posed by squeezing groups of cells into blood and lymphatic vessels (44). Additional examples of collective migrations include blood vessel sprouting, epithelial closures, and innumerable embryonic morphogenetic movements.…”
Section: Discussionmentioning
confidence: 99%
“…43). Collective migration may be the rule rather than the exception in metastasis, despite the physical challenges posed by squeezing groups of cells into blood and lymphatic vessels (44). Additional examples of collective migrations include blood vessel sprouting, epithelial closures, and innumerable embryonic morphogenetic movements.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fate of cancer cells, a malignant cell will meet and surpass various pressures during cancer progression. According to a mouse model, recurrence of a primary tumor demands multiple propensities for each clone, such as invasion, local dissemination, vascular embolus, circulating tumor cells, and micrometastasis 42. Therefore, ITH might provide advantages for metastasis.…”
Section: Clonal Selective Factors For Fostering Ithmentioning
confidence: 99%
“…LOH is an immune escape mechanism that is subject to strong microenvironment later in tumor evolution. Subclonal LOH was observed on chromosome 6, which harbored HLA haplotypes, and the number of putative neoantigens presented to T cells was clearly impaired 42. Therefore, cells with a high number of somatic mutations might not present neoantigens and evade the immune response.…”
Section: Clonal Selective Factors For Fostering Ithmentioning
confidence: 99%
“…Presumably, this gives cancer cells an advantage in efficient seeding, given that they have been shown to have higher metastatic potential than single CTCs [13]. Indeed, polyclonal metastases have been documented in prostate cancer, and in mouse models of breast cancer [13,14]. Although CTC clusters retain cell-cell contacts, studies have shown that they are not fully epithelial, but rather, display a hybrid epithelial--mesenchymal phenotype [13,15].…”
Section: Routes Of Invasionmentioning
confidence: 99%